PENGARUH SANITASI HYGIENE DI AREA RESTORAN & MAIN KITCHEN TERHADAP KEPUASAN TAMU DI HARRIS HOTEL & CONVENTIONS MALANG - dewi hermin sutanto (Jurnal Pariwisata Pesona, 2016)
The purpose of this research is to provides an overview of the influence of sanitation hygiene in the restaurant area and main kitchen toward guest satisfaction. The purpose this research is to know the influence of sanitation and hygiene in the restaurant area and main kitchen. Research methodology used in this research was descriptive qualitative. Data analysis technique include data collection, data reduction, data presentation and conclusion. The result obtained from this research is hygiene sanitation condition in the restaurant area and main kitchen that fulfilled the requirement can give guests satisfaction. The qualified hygiene sanitation be able to support employees perfomance at the main kitchen. Sanitation and hygiene are very important to the development of a hotel especially in provide security and comfort and health to the various guest.